Upaya Meningkatkan Keterampilan Menulis Huruf Tegak Bersambung Menggunakan Media Kartu pada Siswa Kelas II SD Negeri 11 Bahagia Panti Kecamatan Panti Kabupaten Pasaman - Nadina Fitria Hanifah; Pipit Firmanti (Lembaga Pengembangan Kinerja Dosen, 2025)
The lack of knowledge among students in reading cursive letters and copying simple sentences into cursive letters has led to low writing skills in second-grade students at SD Negeri 11 Bahagia. This indicates the importance of implementing an approach that can enhance their writing skills. One alternative that can be implemented is the use of card media. Card media is considered effective because it provides visual stimulation that helps students recognize and correctly write cursive letters. This study aims to improve students' ability to write cursive letters through the use of card media in Indonesian language lessons. The research method used is Classroom Action Research (CAR), which allows for direct evaluation in each learning cycle. The subjects of this study are second-grade students at SD Negeri 11 Bahagia Panti. Before the action was implemented, the average score of students in the pre-action activities was 60, indicating the need for improvement. In the first cycle, the average score increased to 75, with a completion percentage of 55%. Although there was an improvement, it did not yet reach the expected target. After continuing to the second cycle, the students' average score further increased to 81.2, with a completion percentage reaching 84%. This shows that the use of card media successfully improved students' writing skills and that the target set had been achieved. Therefore, this study concludes that the use of card media can significantly improve students' learning outcomes in writing cursive letters.